2018
DOI: 10.1021/acs.jmedchem.8b00673
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Tetrahydroisoquinoline Kappa Opioid Receptor Antagonists of Lead Compound (3R)-7-Hydroxy-N-[(1S)-2-methyl-1-(piperidin-1-ylmethyl)propyl]-1,2,3,4-tetrahydroisoquinoline-3-carboxamide (PDTic)

Abstract: Past studies have shown that it has been difficult to discover and develop potent and selective κ opioid receptor antagonists, particularly compounds having potential for clinical development. In this study, we present a structure-activity relationship (SAR) study of a recently discovered new class of tetrahydroisoquinoline κ opioid receptor antagonists which led to (3 R)-7-hydroxy- N-{(1 S)-2-methyl-1-[(-4-methylpiperidine-1-yl)methyl]propyl}-1,2,3,4-tetrahydroisoquinoline-3-carboxamide (12) (4-Me-PDTic). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The Schild analysis showed that 34 has a linear plot with a slope of −0.92, indicating that 34 is likely a competitive antagonist (Figure B,C). An apparent K e value was also calculated using the equation described previously: K e = [ L ]/(( A ′/ A ) – 1), where [ L ] is the test compound concentration, A ′ is the EC 50 value of PEA with 34 , and A is the EC 50 value of PEA alone. ,, In our assay, 34 has an apparent K e value of 4.0 ± 0.6 nM, which is consistent with the estimated pA2 value determined from the Schild plot (5 nM, x -intercept).…”
Section: Resultssupporting
confidence: 81%
“…The Schild analysis showed that 34 has a linear plot with a slope of −0.92, indicating that 34 is likely a competitive antagonist (Figure B,C). An apparent K e value was also calculated using the equation described previously: K e = [ L ]/(( A ′/ A ) – 1), where [ L ] is the test compound concentration, A ′ is the EC 50 value of PEA with 34 , and A is the EC 50 value of PEA alone. ,, In our assay, 34 has an apparent K e value of 4.0 ± 0.6 nM, which is consistent with the estimated pA2 value determined from the Schild plot (5 nM, x -intercept).…”
Section: Resultssupporting
confidence: 81%
“…Apparent K e values were calculated using the equation K e = [L]/((A′/A) -1), where [L] is the concentration of test compound, A′ is the EC 50 value of PEA in the presence of antagonist, and A is the EC 50 value of PEA in the absence of antagonist. 35,37,[39][40][41][42][43] K e values were considered valid when the ER was at least 4. In the curve shift assay, antagonist 1 has a K e value of 110 nM, while antagonist 2 has a K e value of 159 nM.…”
Section: -Well Assay Miniaturizationmentioning
confidence: 99%
“…It is well documented that methyl groups can have a significant effect on the potency of target compounds. , Furthermore, in a recent study, we found that the addition of a methyl group to the 4-position on the piperidine ring of compound 42 to give the 4-methyl analogue 4-MePDTic ( 43 ) resulted in a 18-fold increase in the κ opioid receptor potency relative to 42 ; therefore, we investigated the effect of adding a 4-methyl group to 1 (Table ). Compound 18 , which is the 4-methyl analogue of 1 , has a K e = 1.27 nM at the κ opioid receptor and thus is 9 times less potent than 1 , which has a K e = 0.14 nM at the κ opioid receptor.…”
Section: Resultsmentioning
confidence: 99%
“… a Data are mean ± SEM of at least three independent experiments conducted in duplicate. None of the compounds had agonist activity at 10 μ M. b Taken from ref 22. c 88:12 mixture of isomers by HPLC. d Taken from ref 24. …”
Section: Figurementioning
confidence: 99%